No surrender : a father, a son, and an extraordinary act of heroism that continues to live on today - Edmonds, Chris (Christopher Waring), 1957-; Century, Douglas (HarperOne, an imprint of HarperCollinsPublishers, 2019)
"Part contemporary detective story, part World War II historical narrative, No Surrender is the inspiring true story of Roddie Edmonds, a Knoxville-born enlistee who risked his life during the treacherous final days of World War II to save others from murderous Nazis, and the lasting effects his actions had on thousands of lives--then and now"--Provided by publisher.